2014
DOI: 10.1021/ct4010454
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mutations Alter Dynamics of Inhibitor-Bound HIV-1 Protease

Abstract: Under the selective pressure of therapy, HIV-1 protease mutants resistant to inhibitors evolve to confer drug resistance. Such mutations can impact both the dynamics and structures of the bound and unbound forms of the enzyme. Flap+ is a multidrug-resistant variant of HIV-1 protease with a combination of primary and secondary resistance mutations (L10I, G48V, I54V, V82A) and a strikingly altered thermodynamic profile for darunavir (DRV) binding relative to the wild-type protease. We elucidated the impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…4,8,9,12–14 One well characterized extremely drug resistant isolate of PR bearing 19 mutations (PR20) 10,1517 exhibits 3–4 orders of magnitude weaker binding to clinical PIs relative to the wild-type enzyme. However, it mediates Gag processing only about 4-fold more slowly and retains the same order of cleavage as the wild-type enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,9,12–14 One well characterized extremely drug resistant isolate of PR bearing 19 mutations (PR20) 10,1517 exhibits 3–4 orders of magnitude weaker binding to clinical PIs relative to the wild-type enzyme. However, it mediates Gag processing only about 4-fold more slowly and retains the same order of cleavage as the wild-type enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…This model also allows for the possibility that dynamics of each of the conformational states varies 67, 68 and, as mutations accumulate, the exchange rate among the states also varies. 42, 69 The four conformers of the proposed ensemble are shown in Figure 3 where the most noticeable change in protein structure involves a segmental motion of the β-hairpin flaps (also shown in Figure 1). Each conformer has been observed, to some degree, via X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experimental studies have shown that there is a relationship between conformational sampling and drug resistance in HIV-PR (Cai et al, 2014;Cai et al 2012Foulkes-Murzycki et al, 2013Gibbs, 2014 andde Vera et al, 2013). Therefore, understanding functional dynamics of the flaps of HIV-PR is of great importance to the development of new HIV-PR inhibitors.…”
Section: Introductionmentioning
confidence: 99%